2005
DOI: 10.1093/jat/29.5.296
|View full text |Cite
|
Sign up to set email alerts
|

MDMA and MDA Concentrations in Antemortem and Postmortem Specimens in Fatalities Following Hospital Admission

Abstract: Over the last 15 years, numerous deaths involving "Ecstasy" Differences in concentrations were also observed between anatomical sites, with central sites (e.g., heart) having much higher concentrations than peripheral sites (e.g., femoral). Overall, MDMA and MDA appear to exhibit postmortem redistribution and concentrations measured in postmortem specimens (even from peripheral sites) are not directly comparable with antemortem findings close to or prior to death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 17 publications
1
13
0
2
Order By: Relevance
“…Patel et al found heart samples are likely to be higher than peripheral blood samples [40]. In one of the cases reported by Elliot the heart blood had a concentration of 28.39 mg/l, with a right femoral blood sample of 6.19 mg/l, left femoral blood of 7.25 mg/l and vitreous of 11.93 mg/l [43]. The post-mortem samples were taken 2 days after death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patel et al found heart samples are likely to be higher than peripheral blood samples [40]. In one of the cases reported by Elliot the heart blood had a concentration of 28.39 mg/l, with a right femoral blood sample of 6.19 mg/l, left femoral blood of 7.25 mg/l and vitreous of 11.93 mg/l [43]. The post-mortem samples were taken 2 days after death.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of 5 cases where both ante-mortem and post-mortem samples were available revealed ante-mortem concentraions of MDMA of 0.55-4.33 mg/l with post-mortem values of 0.47 and 28.39 mg/l. [43]. The second problem is that MDMA is subject to post-mortem redistribution, due to its high volume of distribution [44].…”
Section: Discussionmentioning
confidence: 99%
“…that relatively small increases in doses result in disproportional increases in MDMA blood concentrations [19]. Furthermore, femoral blood is generally accepted as the most reliable blood sample for drug analysis in fatalities [20]; however, Elliot [21] has shown that MDMA and MDA exhibit post-mortem redistribution and that the femoral blood concentrations of MDMA and MDA are higher than antemortem findings close to death.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an elevated central blood level may somehow reflect the drug concentration in the heart. The central to peripheral blood concentration ratios have been investigated for various compounds [135][136][137][138] and their values are listed in the table in supplementary material. As drugs diffuse not only from the myocardium but also from other surrounding organs, these data in some cases may be misleading.…”
Section: Introductionmentioning
confidence: 99%